An Analysis of Ecolexicons Found in Selected Petatah Petitih in Nagari Gunuang - Nadhifa Utami; Rusdi Noor Rosa (English Language and Literature, 2022)
Human use language in their interaction in daily life to convey or deliver their thoughts and communicate with each other. This research belonged to the descriptive qualitative research to find out ecolexicons and the description of each ecolexicon based on the knowledge of community in Nagari Gunuang using triple dimension of social praxis. Based on data analysis and discussion found 30 words belonged to ecolexicons. Afterward, the data were classified into three categories biotic flora, biotic fauna, and abiotic. The researcher found 28 biotic lexicons, 22 of them are categorized as flora lexicons and 6 of them are categorized as fauna lexicons. On the other hand, abiotic lexicon was found only 2 by the researcher. Lexicons about biotic flora are considered as the most dominant type of ecolexicons that found. Among 22 biotic flora lexicons, 4 of them are classified as death words because it no longer used in daily life and unrecognized by the informant or society.